THE RESULTS OF TREATMENT OF THE PATIENTS WITH THE RUPTURE OF ABDOMINAL AORTIC ANEURYSMS IN MULTIFIELD HOSPITAL - V. B. Mosyagin; V. F. Rylkov; A. A. Moiseev; I. V. Karpatsky (Вестник хирургии имени И.И. Грекова)
The rupture of infrarenal segment of aorta is the severe pathology in spite of modern diagnostics and the operation. This case is accompanied by negative results of treatment (lethality consists of 56,3%). The article presents the experience of treatment of 157 patients with the rupture of infrarenal segment of aorta in conditions of multifield hospital (Municipal hospital № 26). The authors highlighted the postoperative complications, their influence on negative outcome. It was shown, that the main reasons of negative outcome of such patients with abdominal aortic aneurism, complicated by the rupture, were an advanced age of patients, who had the complex of concomitant diseases and postoperative complications such as nosocomial pneumonia, cardiac problems and multiple organ failure due to massive acute hemorrhage.